2009
DOI: 10.1007/s11010-009-0313-0
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat and apolipoprotein genotypes modulate plasma lipoprotein levels in Brazilian elderly women

Abstract: Studies show that genetic polymorphisms in apolipoproteins, which are in charge of lipid transport, predispose to atherogenic dyslipidemia. This study aimed to investigate the impact of apolipoprotein E, A5, and B genotypes and dietary intake on lipid profile in a sample of elderly women in Brazil. Two hundred and fifty-two women (60 years or older) living in the outskirts of the Brazilian Federal District underwent clinical and laboratory assessments to characterize glycemic and lipidemic variables, and also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 43 publications
1
18
0
1
Order By: Relevance
“…A study with elderly Brazilian women found that triglyceride values were higher in ε2 carriers than in ε4 carriers [34]. In contrast, no obvious relationship between APOE status and serum triglycerides was reported in a study with patients with metabolic syndrome [35], which is in line with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…A study with elderly Brazilian women found that triglyceride values were higher in ε2 carriers than in ε4 carriers [34]. In contrast, no obvious relationship between APOE status and serum triglycerides was reported in a study with patients with metabolic syndrome [35], which is in line with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…However, an abbreviated 4-hour PPL test seems to be a valid surrogate for an 8-hour test 32. Finally, variations in genes such as those encoding the apolipoproteins A, B and E may directly affect PPL due to their involvement in lipid metabolism 31,33. Therefore, studies using longer postprandial times and examining allelic variations should be conducted to better understand the different PPL mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Participants included community-dwelling elderly women participating in the ongoing program established by the Catholic University of Brasília, Brazil, and the geriatric service of its university hospital to promote preventive health actions for the elderly population [19,20] . Following inspection of medical records, patients were excluded if any of the following were present: noncontrolled type 2 diabetes, obesity, having smoked more than 100 cigarettes in their lifetime and/or having drunk at least one dose (12 g) of alcohol per week within the past 12 months.…”
Section: Participants and Methodsmentioning
confidence: 99%